Artificial intelligence in cyber-physical systems principles and applications - Kumar Sagar, Anil (CRC Press, 2023)
Artificial Intelligence (AI) and the Internet of Things (IoT) are growing rapidly in today’s business world. In today's era, 25 billion devices, including machines, sensors, and cameras, are connected and continue to grow steadily. It is assumed that in 2025, 41.6 billion IoT devices will be connected, generating around 79.4 zettabytes of data.IoT and AI are intersecting in various scenarios. IoT-enabled devices are generating a huge amount of data, and with the help of AI, this data is used to build various intelligent models. These intelligent models are helpful in our daily lives and make the world smarter. Artificial Intelligence in Cyber Physical Systems: Principles and Applications addresses issues related to system safety, security, reliability, and deployment strategies in healthcare, military, transportation, energy, infrastructure, smart homes, and smart cities
Keywords: bicssc / Robotics; bicssc / Information technology - general issues; bicssc / Electrical engineering; bicssc / Transport technology & trades; bicssc / Communications engineering / telecommunications; bicssc / Software Engineering; bisacsh / COMPUTERS / Internet of Things; bisacsh / COMPUTERS / Machine Theory; bisacsh / TECHNOLOGY & ENGINEERING / Electrical; bisacsh / TECHNOLOGY & ENGINEERING / Electronics / General